2014
DOI: 10.1007/978-94-007-7155-0_13
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Probability Education: Perceptual Judgment as Epistemic Resource

Abstract: The mathematics subject matter of probability is notoriously challenging, and in particular the content of random compound events. When students analyze experiments, they often omit to discern variations as distinct outcomes, e.g., HT and TH in the case of flipping a pair of coins, and thus infer erroneous predictions. Educators have addressed this conceptual difficulty by engaging students in actual experiments whose outcomes contradict the erroneous predictions. Yet whereas empirical activities per se are cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Consistent with the concreteness fading approach, another route for the grounded cognition approach in pedagogical simulations is to employ tangible objects before students transition to computer simulations. Examples of such objects have included marbles for drawing samples from a box (Abrahamson, 2014, van Dijke-Drookers et al, 2021b, different-colored candies to demonstrate sampling distributions (Hancock & Rummerfield, 2020), a video demonstration of an instructor manually shuffling data on paper to teach the randomization test function in R (Zhang et al, 2022), and data cards in a population bag (Arnold et al, 2017). Although many studies did not evaluate the particular impact of these tangibles on learning, Hancock and Rummerhield's quasi-experiment revealed that the group that engaged with tangible activities before computer simulations had significantly higher improvement in their exam scores compared to the group that engaged with only computer simulations.…”
Section: Grounded Simulation Designsmentioning
confidence: 99%
“…Consistent with the concreteness fading approach, another route for the grounded cognition approach in pedagogical simulations is to employ tangible objects before students transition to computer simulations. Examples of such objects have included marbles for drawing samples from a box (Abrahamson, 2014, van Dijke-Drookers et al, 2021b, different-colored candies to demonstrate sampling distributions (Hancock & Rummerfield, 2020), a video demonstration of an instructor manually shuffling data on paper to teach the randomization test function in R (Zhang et al, 2022), and data cards in a population bag (Arnold et al, 2017). Although many studies did not evaluate the particular impact of these tangibles on learning, Hancock and Rummerhield's quasi-experiment revealed that the group that engaged with tangible activities before computer simulations had significantly higher improvement in their exam scores compared to the group that engaged with only computer simulations.…”
Section: Grounded Simulation Designsmentioning
confidence: 99%
“…Probability is a challenging lesson for students especially in compound events. They tend to make incorrect predictions of events http://journals.ums.ac.id/index.php/jramathedu (Abrahamson, 2014) so that many students have difficulty learning probability. They find it tricky to connect theoretical and empirical contexts (Nilsson, 2014).…”
Section: Introductionmentioning
confidence: 99%